Practice for Life - Cuba, Lee. (Cambridge, MA : Harvard University Press, 2016)
Undergraduates do not experience college as having a clear beginning and end. Their engagement with higher education is at best episodic. But as Practice for Life shows, the disruptions provide opportunities for reflection and course-correction as students learn to navigate the future uncertainties of adulthood.
Frontmatter -- Contents -- Preface -- One. Restarting College -- Two. Time -- Three. Connection -- Four. Home -- Five. Advice -- Six. Engagement -- Seven. Practice for Life -- Appendix -- Notes -- Acknowledgments -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed Feb. 24, 2017)
Keywords: Academic achievement -- Economic aspects -- United States; College students -- United States -- Attitudes; Decision making -- Psychological aspects; Education, Higher -- United States -- Evaluation